L-Carnitine and Pyruvate Are Prosurvival Factors During the Storage of Stallion Spermatozoa at Room Temperature. Issue 4 (1st October 2015) - Gibb, Zamira; Lambourne, Sarah R.; Quadrelli, Julianne; Smith, Nathan D.; Aitken, Robert J.
Abstract: The spermatozoa of many stallions do not tolerate being cooled, restricting the commercial viability of these animals and necessitating the development of a chemically defined room temperature (RT) storage medium. This study examined the impact of two major modulators of oxidative phosphorylation, pyruvate (Pyr) and L-carnitine (L-C), on the storage of stallion spermatozoa at RT. Optimal concentrations of Pyr (10 mM) and L-C (50 mM) were first identified and these concentrations were then used to investigate the effects of these compounds on sperm functionality and oxidative stress at RT. Mitochondrial and cytosolic reactive oxygen species, along with lipid peroxidation, were all significantly suppressed by the addition of L-C (48 h MitoSOX Red negative: 46.2% vs. 26.1%; 48 and 72 h dihydroethidium negative: 61.6% vs. 43.1% and 64.4% vs. 46.9%, respectively; 48 and 72 h 4-hydroxynonenal negative: 37.1% vs. 23.8% and 41.6% vs. 25.7%, respectively), while the Pyr + L-C combination resulted in significantly higher motility compared to the control at 72 h (total motility: 64.2% vs. 39.4%; progressive motility: 34.2% vs. 15.2%). In addition, supplementation with L-C significantly reduced oxidative DNA damage at 72 h (9.0% vs. 15.6%). To investigate the effects of L-C as an osmolyte, comparisons were made between media that were osmotically balanced with NaCl, choline chloride, or L-C. This analysis demonstrated that spermatozoa stored in the L-C balanced medium had significantly higher total motility (55.0% vs. 39.0%), rapid motility (44.0% vs. 25.7%), and ATP levels (70.9 vs. 12.8 ng/ml) following storage compared with the NaCl treatment, while choline chloride did not significantly improve these parameters compared to the control. Finally, mass spectrometry was used to demonstrate that a combination of Pyr and L-C produced significantly higher acetyl-L-carnitine production than any other treatment (6.7 pg/10 6 spermatozoa vs. control at 4.0 pg/10 6 spermatozoa). These findings suggest that Pyr and L-C could form the basis of a novel, effective RT storage medium for equine spermatozoa.